2008
DOI: 10.1029/2008ja013098
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐instrument analysis of electron populations in Saturn's magnetosphere

Abstract: [1] We analyze the radial distribution of electron populations inside 20 R s in Saturn's magnetosphere, and we calculate moments for these populations by a forward modeling method using composite spectra produced by the CAPS/ELS (0.6 eV to 26 keV) and the MIMI/LEMMS (15 keV to 10 MeV) instruments on board Cassini. We first calculate and harmonize both data sets in physical units and apply corrections taking into account biases introduced by spacecraft interaction with the magnetospheric environment. We then te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
347
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 367 publications
(380 citation statements)
references
References 33 publications
33
347
0
Order By: Relevance
“…This low energy electron density is consistent with in situ measurements made by the Cassini spacecraft (Schippers et al 2008). The amount of water involved in all of the models above is equivalent to an ice cube several tens of metres in size.…”
Section: Introduction: Feasibility Of Water Maser Detection In the Sasupporting
confidence: 73%
“…This low energy electron density is consistent with in situ measurements made by the Cassini spacecraft (Schippers et al 2008). The amount of water involved in all of the models above is equivalent to an ice cube several tens of metres in size.…”
Section: Introduction: Feasibility Of Water Maser Detection In the Sasupporting
confidence: 73%
“…Chotoo et al 2000;Mann et al 2002;Zouganelis et al 2004;Maksimovic et al 2005;Marsch 2006; Yoon et al 2006;Pierrard and Lazar 2010), and planetary magnetospheres (e.g. Christon 1987;Collier and Hamilton 1995;Mauk et al 2004;Schippers et al 2008;Dialynas et al 2009;Ogasawara et al 2012), (2) the outer heliosphere and the inner heliosheath (e.g. Decker and Krimigis 2003;Decker et al 2005;Heerikhuisen et al 2008Livadiotis et al 2011Livadiotis et al , 2013Livadiotis and McComas 2012a), and (3) other various plasma-related analyses (e.g.…”
mentioning
confidence: 99%
“…Upward currents are potentially associated with downward accelerated electrons and bright aurora. This outer magnetospheric region is that dominated by hot tenuous plasma, rather than by cool dense plasma characteristic of the inner region (Schippers et al, 2008;Sergis et al, 2009;Kellett et al, 2010Kellett et al, , 2011.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%
“…They found that the region of upward current, which may be associated with downward electron acceleration and UV auroras, maps to the closed field region between the boundary of open field lines and the outer edge of the ring current. We also note that the plasma in this outer region is dominated by hot (several keV and above) tenuous (∼0.1 cm −3 ) ions and electrons, rather than the cool (∼100 eV ions and few eV electrons) dense (up to ∼100 cm −3 ) water plasma originating from Enceladus that is characteristic of the inner region (Schippers et al, 2008;Sergis et al, 2009;Kellett et al, 2010Kellett et al, , 2011.…”
Section: Image C During Northward Imf Conditionsmentioning
confidence: 99%